In vitro Micropropagation of Pomegranate (Punica granatum L.) Derived from Cotyledon (Plant Tissue Culture and Biotechnology, 2021)
A high frequency in vitro plant regeneration of pomegranate was established on MS medium supplemented with different concentrations and combinations of plant growth regulators. As explant cotyledons were employed for this study. Ninety percent of the cultured explants responded to form shoots from 30 days old in vitro raised seedlings after 90 days of culture initiation in MS containing 1.0 mg/l IBA + 0.1 mg/l NAA. The average number of shoots per explant was 10.0 ± 2.20, shoot length of 12.0 ± 2.40 cm, node per regenerated shoot was 9.0 ± 1.60 and the leaf number was14.0 ± 1.40. Well developed shoots were cultured on half strength of MS medium supplemented with 0.5 mg/l IBA, in which 90% shoot induced roots implanted after one month. The average number of root per shoot was 8.0 ± 0.90 and the average root length of 6.5 ± 0.40 cm was observed in this medium. Eighty percent plantlets were survived in the outdoor condition during the acclimatization period of seven days.Plant Tissue Cult. & Biotech. 31(1): 61-69, 2021 (June)